The Influence of Online Customer Reviews, Brand Reputation, and Brand Trust on the Purchase Intention of Somethinc Skincare Products on Shopee - Anggraini, Wahyu Putri; Kussudyarsana (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This research aims to analyze the influence of online customer reviews, brand reputation, and brand trust on the purchase intention of Somethinc skincare products on Shopee. Using a quantitative approach and purposive sampling, the study collected primary data from 160 respondents residing in Surakarta who own a Shopee account and are familiar with Somethinc but have never purchased its products. Data analysis was conducted using SPSS version 25, employing validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that online customer reviews, brand reputation, and brand trust each have a positive and significant effect on purchase intention. Positive online reviews, a strong brand reputation, and high consumer trust significantly enhance the likelihood of purchasing Somethinc skincare products. However, the research is limited by its sample area and the number of variables analyzed. Future research is recommended to involve broader geographic samples and explore additional influencing factors to obtain more generalized findings.